Hormonal parameters and genetic polymorphism at norm and neurotic stress-related disorders - L. A. Ryadovaya; Ye. V. Gutkevich; S. A. Ivanova; V. Ya. Semke; Ye. M. Yepanchintseva (Бюллетень сибирской медицины, 2008)
The concentrations of steroid and thyreoid hormones and polymorphic variants of genes 5-HTR2A and 5-HTT at patients with dissociative (conversion) disorders, patients with adjustment disorders and mentally healthy persons has beeng studied. We revealed the hormonal peculiarities and genetic polymorphisms.